Correspondence: predictors of prognosis in neonates with congenital diaphragmatic hernia - Authors' reply - Catarina Granjo Morais; Gustavo Rocha; Filipa Flor-; Paulo Éden; Ana Catarina Fragoso; Hercília Guimarães (Hygeia Press di Corridori Marinella, 2017)
We would like to start by thanking the author for his kind correspondence and his comments on our paper.   This corrispondence refers to the following article: Granjo Morais C, Rocha G, Flor-de-Lima F, Éden P, Fragoso AC, Guimarães H. Predictors of prognosis in neonates with congenital diaphragmatic hernia: experience of 12 years. J Pediatr Neonat Individual Med. 2017;6(1):e060126. doi: 10.7363/060126. Comments can be found in the following article: Kumar J. Correspondence: predictors of prognosis in neonates with congenital diaphragmatic hernia. J Pediatr Neonat Individual Med. 2017;6(1):e060139. doi: 10.7363/060139.